2019
DOI: 10.1038/s41438-019-0173-z
|View full text |Cite
|
Sign up to set email alerts
|

TGase positively regulates photosynthesis via activation of Calvin cycle enzymes in tomato

Abstract: Transglutaminases (TGases), which are widespread cross-linking enzymes in plants, play key roles in photosynthesis and abiotic/biotic stress responses; however, evidence concerning the genetics underlying how TGase improves the capability of photosynthesis and the mechanism of TGase-mediated photosynthesis are not clear in this crop species. In this study, we clarified the function of TGase in the regulation of photosynthesis in tomato by comparing wild-type (WT) plants, tgase mutants generated by the CRISPR/C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 52 publications
3
23
0
Order By: Relevance
“…FBPase enzyme contributes a key role for the regeneration of ribulose-1,5-bisphosphate (RuBP) in the Calvin cycle. Our recent research showed that TGaseOE plants significantly elevated both FBPase activity and its encoding gene expression and the speed of electron transport for the production of RuBP is more in comparison to WT plants under optimal growth conditions (Zhong et al, 2019a). Similarly, our results showed that TGaseOE plants had higher expression level of FBPase both in control and heat stress (Table S8).…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…FBPase enzyme contributes a key role for the regeneration of ribulose-1,5-bisphosphate (RuBP) in the Calvin cycle. Our recent research showed that TGaseOE plants significantly elevated both FBPase activity and its encoding gene expression and the speed of electron transport for the production of RuBP is more in comparison to WT plants under optimal growth conditions (Zhong et al, 2019a). Similarly, our results showed that TGaseOE plants had higher expression level of FBPase both in control and heat stress (Table S8).…”
Section: Discussionsupporting
confidence: 75%
“…Ailsa Craig) seedlings were used as test material in this experiment. Two independent homozygous TGase overexpressed (TGaseOE) lines were obtained from our laboratory (Zhong et al, 2019a). Germinated seeds were sown in a 50-holes seedling tray filled with peat and vermiculite mixture (2:1, v:v) and transferred to it artificial growth chamber.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, reduction of biomass under Hg stress may be the consequence of reduction in photosynthesis pigments and following blocking of photosynthesis. Declined Pn may result from the inhibition of relevant reaction steps in the Benson-Calvin cycle and rubisco activity influenced by these contaminants [31]. Moreover, a decrease in Pn could be due to stomatal closing.…”
Section: Damage Of Photosynthesis Resulting From Hg Toxicity Accounted For the Sick Growthmentioning
confidence: 99%
“…9 After germination, seedlings were hydroponically grown in Hoagland's nutrient solution at a temperature of 25/20 °C (day/ night), a light intensity of 200 μmol m −2 s −1 , and a 12/12 h day/night rhythm. 12 Six tomato seedlings with approximative growth at two-leaf stage were transplanted in each 2 L plastic pot; the nutrient solution was renewed every 2 days. 12 When the seedlings were in the three-leaf one-heart stage, the acute toxicity test set the root exposure concentrations of 0, 2, 4, 6, and 8 mg/L FSF for 24 h. 2,8,13 The long-term experiment with continuous exposure for 7 d set a series of concentrations of 0, 0.5, 1, and 2 mg/L in the nutrient solutions.…”
Section: Methodsmentioning
confidence: 99%